Implication of Problem-Based Scenarios on Students' ESD Anticipatory Competency on the Concept of Environmental Change - Silmi Aliya Zahra Sudarya; Suhendar Suhendar; Setiono Setiono (BIOEDUKASI, 2023)
This study aims to determine the effect of problem-based scenarios on students' ESD Anticipatory Competency on environmental change material. It is motivated by the difficulty of students when asked to respond to future events, and further research needs to be done on the right learning model to equip Anticipatory Competency. So the learning model used in this study is Problem-Based Scenarios. The type of research used is quasi-experiment with Non Equivalent Control Group Design. The research sample was selected using purposive sampling, class X IPA as an experimental class of 19 students and X IPS-2 as a control class with 18 students. The instruments used in this study were Anticipatory Competency questions consisting of 5 essay questions, and a questionnaire for students' responses to Problem-Based Scenarios consisting of 10 statements. The results of the study based on hypothesis testing obtained a significance value of Sig (2-tailed) of 0.000, then H0 is rejected and H1 is accepted. The results of the students' response questionnaire regarding the use of Problem-Based Scenarios showed an average score in the excellent category (81-100). The results of the instrument in this study indicate that problem-based scenarios affect the Anticipatory Competency of students on Environmental Change material.